Social preferences under risk: Ex-post fairness vs. efficiency - Alexia Gaudeul (Friedrich Schiller University Jena, 2015)
Social lotteries are lotteries that are played along with someone else. The experimental literature indicates that risk attitudes depend on how one's situation in the safe alternative compares to that of a peer. Evaluation of the risky alternative also depends on whether the lottery gives equal payoffs ex-post. Experiments usually present payoffs side-by-side (payoff for me, payoff for the other). This draws attention to inequality in payoffs and thus gives weight to fairness concerns. We consider whether showing own payoff as a share of the total payoff changes risk preferences. Showing total payoffs explicitly draws attention to risk at the level of the pair and may thus moderate dislike for negatively correlated lotteries, as those are less risky at the level of the group. We find that a significant minority of subjects keeps on disliking lotteries that lead to ex-post unequal distributions of payoffs. Subjects also tend to prefer taking a risk rather than obtaining safe but unequal payoff distributions. Beyond reconciling findings from the previous literature, we also discuss differences in sensitivity to the social setting across individuals and the relation between social value orientation in safe and in risky settings.
Keywords: C91; D63; D81; 330; altruism; choice under risk; efficiency; experiment; fairness; inequality aversion; lotteries; social lotteries; social preferences